Absolute Velocity and Total Stellar Aberration(II) - Cojanovic, Milos (JOURNAL OF ADVANCES IN PHYSICS, 2020)
In this paper, we will show that in addition to measuring annual and diurnal stellar aberration it is also possible 7 directly to measure the angle of secular aberration caused by the motion of the solar system relative to other 8 stars. In the manuscript [1] we dealt with this problem and gave a short description of a special telescope. Using 9 such a telescope we would be able to measure the exact position of the cosmic objects and thus eliminate errors 10 that occur due to the stellar aberration. Assuming that the tube of the telescope is filled with some optical 11 medium [2], we will show that this does not significantly affect the measurement of the stellar aberration angle, 12 but also that these differences are still large enough to enable us to determine the velocity at which the solar 13 system moves relative to the other stars.